Heaphy : Explorer, Artist, Settler. - Sharp, Iain (Auckland University Press, 2008)
Richly illustrated with Charles Heaphy's remarkable paintings and drawings as well as photographs and maps from the period, this engaging work tells the story of Heaphy's life and his art. A draughtsman, explorer, surveyor, gold agent, geologist, soldier, war hero, politician, land commissioner, and judge?even by the versatile standards of Victorian pioneers, Charles Heaphy had an unusually varied career. His biography tells as much about his own life as it does of the settlement of New Zealand. From his earliest surviving watercolor of bird life in 1839 to his last-known sketch.